Correlation between inhomogeneity in polyacrylonitrile spinning dopes and carbon fiber tensile strength. Issue 3 (9th November 2018) - Raghavan, Vijay; Gulgunje, Prabhakar V.; Gupta, Kishor K.; Kamath, Manjeshwar G.; Liu, Yaodong; Pramanik, Chandrani; Newcomb, Bradley A.; Chae, Han Gi; Kumar, Satish
Abstract : The nano‐scale and micro‐scale inhomogeneity of polyacrylonitrile (PAN) spinning dopes obtained from dynamic light scattering (DLS) experiment is correlated with the tensile strength of the resulting carbon fiber. The nanoscale inhomogeneity was estimated by calculating the diffusion coefficients from the slow relaxation mode of polymer solutions in DLS. The nanoscale inhomogeneity in the spinning dopes was found to be in the range of 1–45 nm. We also demonstrate mean of the count rate (MCR) obtained from DLS of PAN solution as a tool to detect the microscale inhomogeneity in the spinning dope for the first time. The MCR of spinning dopes varied from 10.0 to 77.5 kcps (kilo‐counts per second). The tensile strength of carbon fibers from the precursor fiber spun from the spinning dopes in this study varied from 3 to 5.2 GPa. Correlation studies show that the microscale inhomogeneity in the spinning dope was a major contributor to the decrease in the tensile strength of carbon fibers in the range of 3–4.5 GPa. Contaminants causing microscale inhomogeneity in PAN powder were removed by using micelles, reverse micelles and frothing. The surfactant treated PAN polymer was characterized using a fourier transform infrared spectroscope, differential scanning calorimeter, and thermal gravimetic analyzer to demonstrate complete removal of surfactants. POLYM. ENG. SCI., 59:478–482, 2019. © 2018 Society of Plastics Engineers